Emotion activity education assistance program for therapists and psychologists: Efforts to train emotional regulation skills in children with special needs - Saniatuzzulfa, Rahmah; Hakim, Moh. A.; Wicaksono, Bagus; Nugroho, Arista Adi; Agustina, Laelatus Syifa Sari Agustina; Scarvanovi, Berliana Widi; Kusumawati, Rafika Nur; Mardhiyah, Zahrina (Cognicia, 2023)
Abstrak. One of the problems Children with Special Needs that needs to be addressed is the ability of children with special needs to recognize various kinds of emotions as well as how to manage the emotions they are feeling so that children with special needs can adjust to all situations they face. This community service activity aims to provide educational assistance to therapists and psychologists for service partners how to train emotional regulation skills in children with special needs using emotional activity media. The goal is that therapists and psychologists can train emotional regulation skills in children with special needs using instruments that are easy to apply, interesting, and fun. This assistance is carried out by using socialization methods and simulating the practice of using emotional activity media to therapists and psychologists. The activity went smoothly and was full of enthusiasm from the participants. Therapists and psychologists are able to understand the importance of emotional regulation skills in children with special needs and know easy, interesting, and fun learning methods for children with special needs. Keywords : Children with special needs, emotional activities, emotional regulation